First-Principles Study of MoS2, WS2, and NbS2 Quantum Dots: Electronic Properties and Hydrogen Evolution Reaction - Omar H. Abd-Elkader; Hazem Abdelsalam; Mahmoud A. S. Sakr; Abdallah A. Shaltout; Qinfang Zhang (Crystals, 2023)
The electronic and catalytic properties of two-dimensional MoS2, WS2, and NbS2 quantum dots are investigated using density functional theory investigations. The stability of the considered structures is confirmed by the positive binding energies and the real vibrational frequencies in the infrared spectra. The ab initio molecular dynamics simulations show that these nanodots are thermally stable at 300 K with negligible changes in the potential energy and metal–S bonds. The pristine nanodots are semiconductors with energy gaps ranging from 2.6 to 3 eV. Edge sulfuration significantly decreases the energy gap of MoS2 and WS2 to 1.85 and 0.75 eV, respectively. The decrease is a result of the evolution of low-energy molecular orbitals by the passivating S-atoms. The energy gap of NbS2 is not affected, which could be due to the spin doublet state. Molecular electrostatic potentials reveal that the edge sulfur/transition metal atoms are electrophilic/nucleophilic sites, while the surface atoms are almost neutral sites. MoS2 quantum dots show an interestingly low change in the hydrogen adsorption free energy ~0.007 eV, which makes them competitive for hydrogen evolution catalysts.